The relationship between sleep and depression and bipolar disorder in children and young people. Issue 1 (14th January 2022) - Comsa, Monica; Anderson, Kirstie N.; Sharma, Aditya; Yadav, Vanishri C.; Watson, Stuart
Abstract : Background: Sleep difficulties are often reported in practice, and are part of the diagnostic criteria for depression and bipolar disorder. Aims: To inform the understanding of the relationship between sleep and both depression and bipolar disorder. Method: We conducted a narrative literature review of affective disorders and sleep difficulties in children and young people. Results: Specific sleep disorders, such as parasomnias, narcolepsy and sleep-related movement disorders, are associated with depression, whereas insomnia, obstructive sleep apnoea and circadian rhythm disorders are associated with both depression and bipolar disorder in children and young people. Conversely, children and young people with depression can present with a number of sleep difficulties, and these are associated with higher depression severity and greater fatigue, suicidal ideation, physical complaints, pain and decreased concentration. Sleep disturbances among adolescents with bipolar disorder can affect the severity of depressive and manic symptoms, are a poor prognostic indicator and have been associated with social and academic impairment. Antidepressants and antipsychotics can directly affect sleep architecture, which clinicians need to be aware of. Non-pharmacological interventions for sleep problems could prevent and/or minimise the risk of relapse in affective disorders. Conclusions: Sleep difficulties can occur before, during and after an episode of depression or bipolar disorder, and have a higher prevalence in affective disorders compared with the general population. A multi-modal approach would include the treatment of both the affective and specific sleep disorder. Further research is needed in this field to understand the impact of combined interventions on clinical outcomes.